Development of a Brief Multicultural Version of the Test of Mobile Phone Dependence (TMDbrief) Questionnaire - Chóliz, Mariano; Pinto, Lourdes; Phansalkar, Sukanya S.; Corr, Emily; Mujjahid, Ayman; Flores, Conni; Barrientos, Pablo E. (Frontiers in Psychology, 2016)
The Test of Mobile Phone Dependence (TMD) questionnaire (Chóliz, 2012) evaluates the main features of mobile phone dependence: tolerance, abstinence syndrome, impaired impulse control, associated problems, excessive use, etc. Objective: The objective of this study was to develop a multicultural version of the TMD (TMDbrief) adapted to suit the novel communication tools of smartphones. Procedure: In this study, the TMD was completed by 2,028 young respondents in six distinct world regions: Southern Europe, Northwest Europe, South-America, Mesoamerica, Pakistan, and India. Results: Psychometric analysis of the reliability of the instrument and factor analysis were performed to adapt the TMDbrief for use in these regions. Differences among regions with respect to TMD Mobile Phone Dependence scores were obtained. Conclusions: A brief questionnaire for the evaluation of mobile phone addiction in cross-cultural studies was successfully developed.